Work Family Balance and Intention of IT Professionals to Stay in Sri Lanka: The mediating effect of Job Stress - Gamage, Prasadini N.; Heroth, H.M.A.D.K (Gyan Management Journal, 2013)
This research is an attempt to examine the relationship between job related factors and intention to stay among IT Professionals in Sri Lanka, which isa continuous challenge for IT companies in Sri Lanka. In this study four keyestablishmentsofjob related factors as career development, work life balance,job stress and pay satisfaction have been selected to analyse and evaluate their effects on IT professionals’ intention to stay in the current employment. The objectives of the study include identifying the relationship of intention to stay with work life balance. Furthermore, it was decided to identify mediation effect ofjob stress between the relationship work life balance and intention to stay as well. Two hypotheses were formulated in this research. The data was collected from a randomly selected sample of 100 IT professionals in IT companies in Sri Lanka. A structured questionnaire was administered to collect data. The data was analysed using Pearson Correlation Coefficient and Sobel test. The hypotheses were confirmed by the findings of the study. The results of the study exhibited that reducing job related stress from professionals, implementing good work life balance policies increases the intention to stay among IT Professionals.